Approval of price escalation for aluminum windows by BUCG - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of price escalation for aluminum windows by BUCG of Brac University new campus project.